Identity and Entrepreneurship: A Review of the Literature - Herrera, Jaime Andrés Ararat; Urrego, Jackeline Andrea Macias; Mangones, Alejandra Otero (Journal of Ecohumanism, 2025)
This article analyzes the scientific literature produced in the last ten years on the contributions of identity theory in the understanding of entrepreneurship through a bibliographic review that included three parts: collection, analysis and synthesis. From which a final sample of 77 articles was obtained, where three main perspectives were identified: personal, social and identity construction and the use of narrative and discursive methodologies which broaden our understanding of the entrepreneurial process towards a nuanced description of entrepreneurs and entrepreneurial processes in different social contexts, conceptualizing them beyond an economic phenomenon.